Clinical Efficacy of Auricular Acupressure plus Eye Exercises in the Treatment of Adolescent Pseudomyopia. (28th June 2022) - Zhuang, Zhe; Cui, Ya'Nan; Cai, Guofeng; Liu, Kai; Wang, Hong; Jia, Kunping; Wang, Xiuzhen; Cui, Cheng; Sun, Manchao; Guo, Sihui
Abstract : Objective . To assess the clinical efficacy of auricular acupressure plus eye exercises in the treatment of adolescent pseudomyopia, to discover an easier and safer way to treat pseudomyopia. Methods . Forty adolescent patients with pseudomyopia were randomly recruited and assigned (1 : 1) to receive either eye exercises (single group, including 11 males and 9 females) or auricular acupressure plus eye exercises (combined group, including 12 males and 8 females). The clinical endpoint was the clinical efficacy after 28 days of treatment. Results . The baseline characteristics of the combined group were comparable with those of the single group (P > 0.05 ). Auricular acupressure plus eye exercises was associated with a significantly higher clinical efficacy versus eye exercises alone (P < 0.05 ). Conclusion . Ear acupressure plus eye exercises features promising clinical efficacy in the treatment of adolescent pseudomyopia, effectively arresting the progression of pseudomyopia to true myopia.